Educated Mothers, Well-Fed and Healthy Children? Assessing the Impact of the 1980 School Reform on Dietary Diversity and Nutrition Outcomes of Zimbabwean Children - Makate, Marshall; Makate, C. (Routledge, 2018)
© 2017 Informa UK Limited, trading as Taylor & Francis Group We scrutinise the causal influence of schooling on child dietary diversity and nutrition in Zimbabwe using the exogenous variability in schooling prompted by the 1980 education policy, a natural trial fitting a fuzzy regression discontinuity design. We established that a one-year of learning promotes dietary diversity and nutrition even after accounting for plausible mediating factors. Also, education is more liable to impact dietary practices and nutrition through improvements in health knowledge, literacy, wealth and prenatal care utilisation. These findings suggest that promoting schooling access to girls in resource-poor nations might have far-reaching implications on feeding practices and consequently child nutrition.